PS02.018: MINIMALLY INVASIVE ESOPHAGECTOMY (MIE): FROM HYBRID, TO FULLY MINIMALLY-INVASIVE (MIE) AND TO ROBOTIC ASSISTED MIE (RAMIE): A SINGLE SURGEON ANALYSIS. (14th September 2018) - Tagkalos, Evangelos; Hadzijusufovic, Edin; Matthias Corvinus, Florian; Babic, Benjamin; Lang, Hauke; Grimminger, Peter
Abstract: Background: The incidence of esophageal carcinoma is increasing in the western world and esophageal resection is the essential therapy depending on the tumor stage. Several studies report advantages of minimally invasive esophagectomies (MIE) versus conventional open procedures. The use of totally MIE (thoraco- and laparoscopic) or robotic assisted MIE (RAMIE) compared to the hybrid approaches remain unclear. Methods: Between July 2015 and August 2017, the data of 75 patients with esophageal carcinoma were prospectively registered. 25 were treated with a hybrid MIE (hybrid), another 25 with a totally MIE (MIE) and another 25 with a robotic assisted MIE (RAMIE). All patients were operated by the same specialized surgeon in our center. Demographic data), duration of total hospital- and intensive-care-stay (ICU), number of remote lymph nodes and histopathological R-status, as well as operating times were compared. The complications were assessed according to the Dindo-Clavien classification. Results: The overall 30- and 90-day mortality rate were 0% and 1.33% (1/75) respectively. Hospital stay ( P  = 0.262), ICU stay ( P  = 0.079), number of resected lymph nodes ( P  = 0.863) and R status ( P  = 0.132) did not differ significantly between the groups. However more pneumonias and wound infections ( P  = 0.046 and P  = 0.003 respectively) were found in the hybrid group when compared to the minimally invasive group (MIE und RAMIE). Conclusion: Although the MIE as well as the RAMIE group contained the first 25 patients treated in this clinic with this procedures, comparable results with regard to oncological outcomes and morbidity could be achieved. Additionally the minimally invasive approaches seem to be assosiated with low occurence of pneumonia and wound infects. Disclosure: All authors have declared no conflicts of interest.